Lithium secondary battery

The lithium secondary battery addresses capacity and cycle characteristic issues by using a non-aqueous electrolyte with fluorine-based solvent and high-Ni nickel-based transition metal oxide, enhancing electrolyte impregnation and stability to improve performance.

KR103042550B1Active Publication Date: 2026-11-03LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020200090385
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-22
Filing Date
2020-07-21
Publication Date
2026-11-03
Estimated Expiration
2040-07-21

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries face challenges in securing sufficient capacity and cycle characteristics due to the structural and chemical instability of high-nickel cathode active materials, exacerbated by insufficient electrolyte impregnation and potential imbalance within the electrode.

Method used

A lithium secondary battery design incorporating a non-aqueous electrolyte with a specific ratio of a carbonate-based and fluorine-based organic solvent, along with a cathode containing a high-Ni nickel-based transition metal oxide, improves electrolyte impregnation and stability.

Benefits of technology

The improved electrolyte and cathode composition enhance the battery's room-temperature cycle characteristics and capacity by minimizing unimpregnated areas and preventing transition metal leaching, leading to better performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112020076050217-PAT00002
    Figure 112020076050217-PAT00002
  • Figure 112020076050217-PAT00003
    Figure 112020076050217-PAT00003
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery, specifically comprising: a positive electrode comprising a lithium transition metal oxide represented by Chemical Formula 1; a negative electrode; a non-aqueous electrolyte comprising a lithium salt, a first non-aqueous solvent, and a second non-aqueous solvent; and a separator, wherein the first non-aqueous solvent is a carbonate-based organic solvent, the second non-aqueous solvent is a fluorine-based organic solvent, and the volume ratio of the first non-aqueous solvent to the second non-aqueous solvent is 5:5 to 9:1.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a lithium secondary battery with improved cycle characteristics and capacity characteristics. Background Technology

[0002] With the development of the information society leading to advancements in personal IT devices and computer networks, and the accompanying increase in overall societal dependence on electrical energy, the development of secondary batteries capable of efficiently storing and utilizing electrical energy is emerging as a critical issue.

[0003] In particular, since lithium-ion rechargeable batteries theoretically have the highest energy density and can be miniaturized enough to be applied to personal IT devices, research is actively underway to apply them to various devices, such as electric vehicles and power storage devices.

[0004] Meanwhile, a lithium-ion secondary battery is composed of a negative electrode containing a negative electrode active material, a positive electrode containing a positive electrode active material, an electrolyte containing a lithium salt-containing non-aqueous organic solvent, and a separator.

[0005] Recently, in order to manufacture high-capacity batteries, cathode active materials such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium iron phosphate compounds (LiFePO4), or lithium transition metal oxides in which some of the nickel (Ni) in lithium nickel oxide (LiNiO2) is substituted with cobalt (Co) or manganese (Mn) / aluminum (Al) have been proposed; however, there is a problem in that it is difficult to secure sufficient capacity characteristics with these cathode active materials.

[0006] To address these issues, research is being conducted to produce high-nickel (High-Ni) transition metal oxides in which the nickel content exceeds 60% of the total transition metal content.

[0007] However, as the nickel (Ni) content in the cathode active material increases, the structural and chemical stability of the cathode active material decreases, leading to the leaching of transition metals due to side reactions between the cathode active material and the electrolyte. This phenomenon can be locally exacerbated by potential imbalance within the electrode if the electrolyte impregnation of the electrode is insufficient. Prior art literature

[0008] Korean Published Patent Application No. 2014-0071870 Korean Published Patent Application No. 2016-0011548 The problem to be solved

[0009] The present invention aims to solve the above-mentioned problems by providing a lithium secondary battery with improved room-temperature cycle characteristics and capacity characteristics by including a non-aqueous electrolyte with improved viscosity by including a first organic solvent and a second fluorine-based organic solvent in a specific ratio as a non-aqueous organic solvent, and a cathode containing a high-Ni nickel-based transition metal oxide. means of solving the problem

[0010] According to one embodiment, in order to achieve the above objective, the present invention

[0011] A cathode comprising a lithium transition metal oxide represented by the following chemical formula 1,

[0012] cathode,

[0013] A separator interposed between the anode and the cathode, and

[0014] It comprises a non-aqueous electrolyte comprising a lithium salt, a first non-aqueous solvent, and a second non-aqueous solvent, and

[0015] The above first non-aqueous solvent is a carbonate-based organic solvent, and

[0016] The above second non-aqueous solvent is a fluorine-based organic solvent, and

[0017] A lithium secondary battery is provided in which the volume ratio of the first non-aqueous solvent to the second non-aqueous solvent is 5:5 to 9:1.

[0018] [Chemical Formula 1]

[0019] Li(Ni) a Co b Mn c )O2

[0020] In the above chemical formula 1,

[0021] 0.6≤a≤0.9, 0.05≤b<0.3, 0.05≤c<0.3, a+b+c=1.

[0023] The lithium transition metal oxide represented by the above chemical formula 1 is Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 It can be )O2, specifically Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 It could be O2.

[0025] In addition, the lithium salt may be at least one selected from the group consisting of LiBF4, LiPF6, LiCH3CO2, LiCF3CO2, LiCH3SO3, LiFSI (lithium fluorosulfonyl imide, LiN(SO2F)2), LiTFSI (lithium bis(trifluoromethanesulfonyl) imide, LiN(SO2CF3)2), and LiBETI (lithium bis(perfluoroethanesulfonyl) imide, LiN(SO2C2F5)2), specifically at least one selected from the group consisting of LiFSI, LiTFSI, and LiBETI.

[0026] The volume ratio of the first non-aqueous solvent to the second non-aqueous solvent may be a volume ratio of 5:5 to 8:2, specifically a volume ratio of 5:5 to 7:3.

[0028] In addition, the above-mentioned fluorine-based organic solvent may be a fluorine-containing aromatic organic solvent or a fluorine-containing ether organic solvent represented by the following chemical formula 2.

[0029] [Chemical Formula 2]

[0030] [R1-O-R2] n

[0031] In the above chemical formula 2,

[0032] R1 and R2 are each independently an alkyl group having 1 to 10 carbon atoms that is substituted or unsubstituted with at least one fluorine element, and n is any one integer from 1 to 10.

[0034] Specifically, the fluorine-containing aromatic organic solvent may be at least one selected from the group consisting of monofluorobenzene, 1,2-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, pentafluorobenzene, and hexafluorobenzene, and more specifically, may be at least one selected from the group consisting of monofluorobenzene and 1,2-difluorobenzene.

[0036] In addition, the fluorine-containing ether organic solvent may be 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether or 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether. Effects of the invention

[0037] According to the present invention, by providing a non-aqueous electrolyte with improved viscosity containing a fluorine-based organic solvent having low lithium solubility and a cathode containing a high content of nickel-based transition metal oxide together, the electrolyte impregnation properties of the electrode are improved, thereby enabling the manufacture of a lithium secondary battery with improved room-temperature cycle characteristics and capacity characteristics. Specific details for implementing the invention

[0038] The present invention will be described in more detail below.

[0039] Terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0041] Specifically, in one embodiment of the present invention

[0042] A cathode comprising a lithium transition metal oxide represented by the following chemical formula 1,

[0043] cathode,

[0044] A separator interposed between the anode and the cathode, and

[0045] It comprises a non-aqueous electrolyte comprising a lithium salt, a first non-aqueous solvent, and a second non-aqueous solvent, and

[0046] The above first non-aqueous solvent is a carbonate-based organic solvent, and

[0047] The above second non-aqueous solvent is a fluorine-based organic solvent, and

[0048] A lithium secondary battery is provided that contains the first non-aqueous solvent and the second non-aqueous solvent in a volume ratio of 5:5 to 9:1.

[0049] [Chemical Formula 1]

[0050] Li(Ni) a Co b Mn c )O2

[0051] In the above chemical formula 1,

[0052] 0.6≤a≤0.9, 0.05≤b<0.3, 0.05≤c<0.3, a+b+c=1.

[0054] anode

[0055] First, the anode according to the present invention will be described.

[0056] The positive electrode included in the lithium secondary battery of the present invention can be represented by the above chemical formula 1.

[0057] The lithium transition metal oxide represented by the above chemical formula 1 has a nickel content of 0.60 or more and has a high capacity per weight, so it has the advantage of being able to manufacture a secondary battery with high energy density.

[0058] The lithium transition metal oxide represented by the above chemical formula 1 is Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 It can be )O2, specifically Li(Ni) with a higher nickel (Ni) content 0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 It could be O2.

[0060] Meanwhile, high-capacity transition metal oxides with high nickel content, such as the lithium transition metal oxide represented by Chemical Formula 1 above, Li within the layered structure of the cathode active material during the charge-discharge process +1 Ions and Ni +2 As cation mixing occurs, the structure collapses, resulting in the leaching of transition metals during side reactions between the cathode active material and the electrolyte. This phenomenon can be locally exacerbated by potential imbalance within the electrode if the electrolyte impregnation of the electrode is insufficient within the cell—that is, if unimpregnated regions exist within the cathode.

[0061] Accordingly, in the present invention, as described below, a non-aqueous electrolyte with reduced viscosity is provided together to improve the electrolyte wetting of the electrode, thereby minimizing the un-impregnated area within the anode and preventing the exacerbation of the above-mentioned problems.

[0063] Meanwhile, the anode of the invention can be manufactured and used by conventional methods.

[0064] That is, the anode comprises an anode current collector and an anode composite layer formed on the anode current collector, wherein the anode composite layer can be manufactured by coating an anode slurry, which includes an anode active material and optionally a binder, a conductive material, and a solvent, onto the anode current collector, and then drying and rolling.

[0065] The above positive current collector is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used.

[0066] The above-mentioned positive active material may include a high-content nickel-based lithium transition metal oxide having a nickel content exceeding 60%, such as a lithium transition metal oxide represented by Chemical Formula 1.

[0068] Meanwhile, the above-mentioned positive active material may further include a metal oxide capable of reversible intercalation and deintercalation of lithium in addition to the high-content nickel-based lithium transition metal oxide represented by Chemical Formula 1.

[0069] Representative examples of such metal oxides include lithium-manganese oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt oxides (e.g., LiCoO2, etc.), lithium-nickel oxides (e.g., LiNiO2, etc.), and lithium-nickel-manganese oxides (e.g., LiNi 1-Y Mn YO2(here, 0 <Y<1), LiMn 2-z Ni z O4 (where 0 < Z < 2), etc.), lithium-nickel-cobalt oxides (e.g., LiNi 1-Y1 Co Y1 O2(here, 0 <Y1<1) 등), 리튬-망간-코발트계 산화물(예를 들면, LiCo 1-Y2 Mn Y2 O2(here, 0 <Y2<1), LiMn 2-z1 Co z1 O4 (wherein, 0 < Z1 < 2), etc.) or lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mn r3 M S2 It may further include at least one of )O2(wherein M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg and Mo, and p2, q2, r3 and s2 are each atomic fractions of independent elements, 0<p2<1, 0<q2<1, 0<r3<1, 0<s2<1, p2+q2+r3+s2=1)).

[0070] The above-mentioned positive active material may be included in an amount of 80% to 99% by weight, specifically 93% to 98% by weight, based on the total weight of the solid content in the positive slurry. In this case, if the positive active material content is 80% by weight or less, the energy density may be lowered and the capacity may be reduced.

[0071] The above-mentioned binder is a component that assists in the bonding of the active material and conductive material, etc., and in the bonding to the current collector, and is typically added in an amount of 1% to 30% by weight based on the total weight of the solid content in the anode slurry. Examples of such binders include fluoropolymer-based binders comprising polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders comprising styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose-based binders comprising carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyalcohol-based binders comprising polyvinyl alcohol; polyolefin-based binders comprising polyethylene or polypropylene; and polyimide-based binders. Examples include polyester-based binders and silane-based binders.

[0072] The above conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, carbon powder such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used.

[0073] The above conductive material is typically added in an amount of 1 to 30 weight percent based on the total weight of the solid content in the anode slurry.

[0074] The above solvent may include an organic solvent such as NMP (N-methyl-2-pyrrolidone) and may be used in an amount that results in a desirable viscosity when the above-mentioned positive active material and optionally a binder and a conductive material are included. For example, the solid content concentration in the positive slurry containing the positive active material and optionally a binder and a conductive material may be 10% to 70% by weight, preferably 20% to 60% by weight.

[0076] cathode

[0077] In addition, the lithium secondary battery of the present invention may include a negative electrode manufactured by a conventional method.

[0078] The above cathode comprises a cathode current collector and a cathode composite layer formed on the cathode current collector, wherein the cathode composite layer can be manufactured by coating a cathode slurry, which includes a cathode active material and optionally a binder, a conductive material, and a solvent, onto the cathode current collector, and then drying and rolling.

[0079] The above-mentioned negative current collector generally has a thickness of 3 to 500 μm. Such a negative current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloy may be used. In addition, similar to the positive current collector, fine irregularities may be formed on the surface to strengthen the bonding strength of the negative active material, and it may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics.

[0080] In addition, the negative electrode active material may include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal or an alloy of these metals and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.

[0081] As for the carbon material capable of reversibly intercalating / deintercalating the above lithium ions, any carbon-based negative electrode active material commonly used in lithium-ion secondary batteries may be used without particular limitation, and representative examples include crystalline carbon, amorphous carbon, or a combination thereof. Examples of the above crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the above amorphous carbon include soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke, etc.

[0082] As the above metal or alloy of these metals and lithium, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of these metals and lithium may be used.

[0083] The above metal composite oxides include PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1), and Sn x Me 1-x Me y O z(Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, 2, and 3 elements of the periodic table, halogens; 0 <x≤1; 1≤y≤3; 1≤z≤8) 로 이루어진 군에서 선택되는 것이 사용될 수 있다.

[0084] Materials capable of doping and dedoping the above lithium include Si and SiO x (0 <x≤2), Si-Y 합금(상기 Y는 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 전이금속, 희토류 원소 및 이들의 조합으로 이루어진 군에서 선택되는 원소이며, Si은 아님), Sn, SnO2, Sn-Y(상기 Y는 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 전이금속, 희토류 원소 및 이들의 조합으로 이루어진 군에서 선택되는 원소이며, Sn은 아님) 등을 들 수 있고, 또한 이들 중 적어도 하나와 SiO2를 혼합하여 사용할 수도 있다. 상기 원소 Y로는 Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, 및 이들의 조합으로 이루어진 군에서 선택될 수 있다.

[0085] Examples of the above transition metal oxides include lithium-containing titanium composite oxide (LTO), vanadium oxide, and lithium vanadium oxide.

[0086] The above-mentioned cathode active material may be included in an amount of 80% to 99% by weight based on the total weight of the solid content in the cathode slurry.

[0087] The above binder is a component that assists in the bonding between the conductive material, the active material, and the current collector, and is typically added in an amount of 1 to 30 weight percent based on the total weight of the solid content in the cathode slurry. Examples of such binders include fluoropolymer-based binders containing polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders containing styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose-based binders containing carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, or regenerated cellulose; polyalcohol-based binders containing polyvinyl alcohol; polyolefin-based binders containing polyethylene or polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders.

[0088] The above conductive material may be added in an amount of 1 to 20 weight percent based on the total weight of the solid content in the negative electrode slurry as a component to further improve the conductivity of the negative electrode active material. Such conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, carbon powder such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used.

[0089] The above solvent may include water or organic solvents such as NMP or alcohol, and may be used in an amount that results in a desirable viscosity when the above cathode active material and optionally a binder and a conductive material are included. For example, the solid content concentration in the slurry containing the cathode active material and optionally a binder and a conductive material may be 50% to 75% by weight, preferably 50% to 65% by weight.

[0091] Non-aqueous electrolyte

[0092] The lithium secondary battery of the present invention may include a lithium salt, a first non-aqueous solvent, and a second non-aqueous solvent, and a non-aqueous electrolyte.

[0094] (1) Lithium salt

[0095] The above lithium salts can be those commonly used in electrolytes for lithium secondary batteries without limitation, for example, Li as a cation + It includes, and as anion, F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , ClO4 - , BF4 - , B 10 Cl 10 - , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , AlCl4 - , AlO4 - , CH3SO3 - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 -, (CF3)4PF2 - , (CF3)5PF - , C4F9SO3 - , CF3CF2SO3 - , (FSO2)2N - , (CF3SO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , SCN - and (CF3CF2SO2)2N - At least one selected from the group consisting of can be cited.

[0096] Specifically, the lithium salt may comprise a single substance selected from the group consisting of LiBF4, LiPF6, LiCH3CO2, LiCF3CO2, LiCH3SO3, LiFSI (lithium fluorosulfonyl imide, LiN(SO2F)2), LiTFSI (lithium bis(trifluoromethanesulfonyl) imide, LiN(SO2CF3)2), and LiBETI (lithium bis(perfluoroethanesulfonyl) imide, LiN(SO2C2F5)2) or a mixture of two or more.

[0097] Meanwhile, among the above lithium salts, LiPF6 is generally used in the manufacture of most non-aqueous electrolytes, but it has the disadvantage of lowering discharge output characteristics by forming a resistive layer on the lithium surface due to generating a large amount of HF gas and having relatively large chemical side reactions with lithium. In contrast, LiFSI, LiTFSI, and LiBETI, particularly LiFSI, can secure lower viscosity and higher ionic conductivity compared to LiPF6. Therefore, when included, the viscosity of the non-aqueous electrolyte can be relatively lowered, and additional decomposition reactions can be suppressed by forming a protective layer on the lithium surface, thereby further improving discharge output characteristics.

[0098] Accordingly, the non-aqueous electrolyte of the present invention preferably comprises at least one lithium salt selected from the group consisting of LiFSI, LiTFSI, and LiBETI.

[0099] The concentration of the above lithium salt can be appropriately changed within a range that is typically usable, but in order to obtain the effect of forming a corrosion-preventing film on the electrode surface, it may be included in the electrolyte at 0.8 M to 3.0 M, specifically 1.0 M to 3.0 M, and more specifically 1.5 M to 2.8 M.

[0100] If the concentration of the above lithium salt is less than 0.8M, the effect of improving low-temperature capacity and cycle characteristics during high-temperature storage of the lithium secondary battery is negligible, and if the concentration exceeds 3.0M, the electrolyte impregnation may decrease as the viscosity of the non-aqueous electrolyte increases.

[0102] (2) First non-aqueous solvent

[0103] Meanwhile, the first non-aqueous solvent may include a carbonate-based organic solvent.

[0104] The above carbonate-based organic solvent may include at least one of a cyclic carbonate-based organic solvent and a linear carbonate-based organic solvent so as to minimize decomposition due to oxidation reactions, etc., during the charging and discharging process of a secondary battery and to exhibit desired characteristics together with an additive.

[0106] The above-mentioned cyclic carbonate-based organic solvent is a high-viscosity organic solvent with high ionic conductivity and is known to be a solvent that effectively dissociates lithium salts in the electrolyte due to its high dielectric constant. Representative examples of such cyclic carbonate-based organic solvents include any one or more of the organic solvents selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, and fluoroethylene carbonate (FEC); among these, ethylene carbonate is an example that can maintain stable SEI film passivation ability.

[0107] In addition, the above-mentioned linear carbonate-based organic solvent is an organic solvent having low viscosity and low dielectric constant, and representative examples include any one or more of the organic solvents selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethylmethyl carbonate (EMC), methylpropyl carbonate, and ethylpropyl carbonate, and among these, dimethyl carbonate (DMC), which has a small molecular size and low viscosity characteristics, can be cited.

[0108] The first non-aqueous solvent may be used alone as the linear carbonate organic solvent having low viscosity and low dielectric constant, or as a mixture of the cyclic carbonate organic solvent and the linear carbonate organic solvent. If the cyclic carbonate organic solvent and the linear carbonate organic solvent are mixed and used, it is preferable for the non-aqueous electrolyte of the present invention to use the linear carbonate organic solvent having low viscosity and low dielectric constant in a volume ratio of 5 or more so as to minimize the increase in viscosity. Specifically, the cyclic carbonate organic solvent and the linear carbonate organic solvent may be used in a volume ratio of approximately 0.3:9.7 to 3:7, specifically 0.5:9.5 to 1:9.

[0110] (3) Second non-aqueous solvent

[0111] In addition, the non-aqueous electrolyte of the present invention may include a fluorine-based organic solvent as a second non-aqueous solvent.

[0112] The above fluorinated organic solvent may be a fluorine-containing aromatic organic solvent or a fluorine-containing ether organic solvent represented by the following chemical formula 2.

[0113] [Chemical Formula 2]

[0114] [R1-O-R2] n

[0115] In the above chemical formula 2,

[0116] R1 and R2 are each independently an alkyl group having 1 to 10 carbon atoms that is substituted or unsubstituted with at least one fluorine element, and n is any one integer from 1 to 10.

[0118] Specifically, the fluorine-containing aromatic organic solvent may be at least one selected from the group consisting of monofluorobenzene, 1,2-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, pentafluorobenzene, and hexafluorobenzene, and more specifically, in order to minimize the increase in viscosity of the electrolyte, it may be at least one selected from the group consisting of monofluorobenzene and 1,2-difluorobenzene, which have lower viscosity.

[0120] In addition, the fluorine-containing ether organic solvent represented by the above chemical formula 2 is a linear ether organic solvent in which a number of fluorine elements are substituted, and has low viscosity and low salt solubility, and it is known that as the chain length increases, the viscosity increases and the salt solubility decreases.

[0121] Accordingly, in the above chemical formula 2, R1 is an alkyl group having 2 to 8 carbon atoms substituted with at least one fluorine element, R2 is an alkyl group having 1 to 7 carbon atoms substituted with at least one fluorine element, and n may be one integer from 1 to 5.

[0122] Specifically, to minimize the increase in viscosity of the electrolyte, in the above formula 2, R1 is an alkyl group having 2 to 6 carbon atoms substituted with at least one fluorine element, R2 is an alkyl group having 1 to 5 carbon atoms substituted with at least one fluorine element, and n may be an integer among 1 to 5.

[0123] More specifically, the fluorine-containing ether organic solvent may be 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether represented by the following chemical formula 2-1 of the electrolyte or 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether represented by the following chemical formula 2-2.

[0124] [Chemical Formula 2-1]

[0125]

[0127] [Chemical Formula 2-2]

[0128]

[0130] Currently, most secondary batteries primarily use non-fluorinated carbonate organic solvents, particularly high-viscosity cyclic carbonate organic solvents, as the main solvent for the non-aqueous electrolyte. However, these solvents generally cause problems such as deforming the battery's structure and degrading stability when stored for a long time at high temperatures, as gas is generated due to the oxidation of the electrolyte, leading to cell swelling. Furthermore, the reaction heat generated by the side reaction between the electrode and the non-fluorinated carbonate solvent raises the internal temperature of the battery. When the temperature reaches a level above the ignition point, the high-viscosity cyclic carbonate organic solvent combines with surrounding oxygen, leading to a thermal runaway phenomenon, which causes the secondary battery to ignite and explode.

[0131] Accordingly, the non-aqueous electrolyte of the present invention is characterized by comprising a fluorine-based organic solvent having excellent electrochemical stability together with a non-fluorine-based carbonate organic solvent as the main solvent. That is, the fluorine-based organic solvent has high oxidation stability at room temperature and high temperature, has low viscosity, and Since a stable LiF-containing film is formed even under high voltage, adverse reactions between the non-aqueous electrolyte and the electrode, particularly the anode, can be prevented during operation (charging / discharging) under high voltage or during high-temperature storage.

[0132] In addition, in order to suppress the increase in viscosity of the non-aqueous electrolyte in the present invention, the carbonate-based organic solvent, which is the first non-aqueous solvent, and the fluorine-based organic solvent, which is the second non-aqueous solvent, may be mixed and used in a volume ratio of 5:5 to 9:1, specifically 5:5 to 8:2, specifically 5:5 to 7:3.

[0133] If the volume ratio of the first non-aqueous solvent is less than 5, the amount of carbonate-based solvent used for salt dissociation is reduced, and the ionic conductivity may be lowered. Additionally, if the volume ratio of the carbonate-based organic solvent exceeds 9, that is, if the volume ratio of the fluorine-based organic solvent is less than 1, the viscosity of the electrolyte increases, and consequently, the diffusion effect of Li+ ions may be reduced.

[0134] In other words, by providing a non-aqueous electrolyte mixed in the above ratio, the present invention can secure an ionic conductivity similar to that of a conventional non-aqueous electrolyte composed solely of a carbonate-based organic solvent, while simultaneously improving the impregnation properties of the electrolyte by reducing its viscosity. That is, the viscosity of the non-aqueous electrolyte is lowered while maintaining the dissociation structure between the carbonate-based organic solvent and the lithium salt, and based on this, the degree of dissociation of the lithium salt increases, thereby enhancing the diffusion effect of Li+ ions.

[0136] (4) Third non-aqueous solvent

[0137] Meanwhile, the non-aqueous electrolyte for a lithium secondary battery of the present invention may additionally include at least one organic solvent as a third non-aqueous solvent, such as a linear ester-based organic solvent, a cyclic ester-based organic solvent, an ether-based organic solvent, or an amide-based organic solvent, as needed.

[0138] At this time, the first non-aqueous solvent:third non-aqueous solvent may be included in a volume ratio of 1:0.1 to 0.5 to improve battery capacity.

[0139] The above linear ester-based organic solvent may be selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate, or two or more of these organic solvents, but is not limited thereto.

[0140] The above-mentioned cyclic ester-based organic solvent may be selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, ε-valerolactone, and σ-caprolactone as specific examples, or a mixture of two or more of these, but is not limited thereto.

[0141] In addition, the above ether-based organic solvent may be any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methylpropyl ether, and ethyl propyl ether, or a mixture of two or more of these, but is not limited thereto.

[0143] (5) Additional additives

[0144] The non-aqueous electrolyte included in the lithium secondary battery of the present invention may additionally include additional additives within the non-aqueous electrolyte as needed to prevent the non-aqueous electrolyte from decomposing in a high-voltage environment and causing electrode collapse, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, prevention of overcharging, and suppression of battery expansion at high temperatures.

[0145] These additional additives may include at least one additional additive selected from the group consisting of cyclic carbonate compounds, halogen-substituted carbonate compounds, sulfone compounds, sulfate compounds, phosphate compounds, borate compounds, nitrile compounds, amine compounds, silane compounds, and lithium salt compounds, as representative examples.

[0146] Examples of the above-mentioned cyclic carbonate compounds include vinylene carbonate (VC) or vinylethylene carbonate, which can electrochemically decompose at the anode and cathode surfaces to form a robust SEI film.

[0147] Examples of the above halogen-substituted carbonate compounds include fluoroethylene carbonate (FEC).

[0148] The above sulfone-based compound is a material capable of forming a stable SEI film by a reduction reaction on the cathode surface, and may include at least one compound selected from the group consisting of 1,3-propane sulfone (PS), 1,4-butane sulfone, ethene sulfone, 1,3-propene sulfone (PRS), 1,4-butene sulfone, and 1-methyl-1,3-propene sulfone.

[0149] The above sulfate-based compounds are materials that can form a stable SEI film that does not crack even during high-temperature storage by being electrically decomposed on the cathode surface, and examples include ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyl trimethylene sulfate (MTMS).

[0150] The above phosphate-based compounds may include one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tetramethyl trimethylsilyl phosphate, trimethylsilyl phosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite.

[0151] Examples of the above borate compounds include tetraphenylborate, lithium oxalyl difluoroborate (LiODFB), or LiBOB (lithium bisoxalate toborate (LiB(C2O4)2)).

[0152] The above nitrile-based compound may include at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanitrile, cyclopentane carbonitrile, cyclohexane carbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.

[0153] Examples of the above amine-based compounds include triethanolamine or ethylenediamine, and examples of the above silane-based compounds include tetravinylsilane.

[0154] The above lithium salt-based compound is a compound different from the lithium salt included in the above non-aqueous electrolyte, and may include one or more compounds selected from the group consisting of LiPO2F2 and LiBF4.

[0155] Among these additional additives, if vinylene carbonate, vinylethylene carbonate, fluoroethylene carbonate (FEC), or succinonitrile are included, a more robust SEI film can be formed on the negative electrode surface during the initial activation process of the secondary battery.

[0157] Meanwhile, two or more of the above additional additives may be used in a mixture, and the mixture content of these additional additives may be included in an amount of 0.1 to 50 weight%, specifically 0.1 to 10 weight%, based on the total weight of the non-aqueous electrolyte, and preferably 0.05 to 5 weight%. If the mixture content of the above additional additives is less than 0.1 weight%, the effect of improving the low-temperature capacity, high-temperature storage characteristics, and high-temperature life characteristics of the battery is negligible, and if the mixture content of the above additional additives exceeds 50 weight%, there is a possibility that excessive side reactions may occur in the electrolyte during charging and discharging of the battery. In particular, when the above SEI film-forming additives are added in excess, they may not decompose sufficiently at high temperatures and may remain as unreacted substances or precipitated substances in the electrolyte at room temperature. Accordingly, side reactions that degrade the lifespan or resistance characteristics of the secondary battery may occur.

[0159] separator

[0160] In the lithium secondary battery of the present invention, the separator separates the negative electrode and the positive electrode to prevent internal short circuits and impregnates a non-aqueous electrolyte to provide a pathway for the movement of lithium ions. While any separator typically used as a separator in a lithium secondary battery may be used without special limitations, it is specifically desirable that it has low resistance to the movement of lithium ions in the electrolyte and excellent electrolyte absorption capability.

[0161] The above separator can be formed by mixing a polymer resin, a filler, and a solvent to prepare a separator composition, and then directly coating and drying the separator composition on top of an electrode to form a separator film, or by casting and drying the separator composition on a support and then laminating the separator film peeled from the support onto top of the electrode.

[0162] Specifically, the separator may be used as a single porous polymer film made of a polyolefin-based polymer, such as a commonly used porous polymer film, for example, an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or by laminating two or more layers thereof, or a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting-point glass fibers, polyethylene terephthalate fibers, etc., may be used. In addition, a coated separator containing a ceramic component or a polymer material may be used to ensure heat resistance or mechanical strength.

[0163] The pore diameter of the porous separator may generally be 0.01 to 50 μm, and the porosity may be 5 to 95%. In addition, the thickness of the porous separator may generally be in the range of 5 to 300 μm.

[0165] The external shape of the lithium secondary battery of the present invention is not particularly limited, but can be a cylindrical shape using a can, a prismatic shape, a pouch shape, or a coin shape.

[0167] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the invention. However, the embodiments according to the present invention may be modified in various different forms, and the scope of the present invention should not be interpreted as being limited to the embodiments described below. The embodiments of the present invention are provided to more completely explain the invention to those with average knowledge in the art.

[0169] Examples

[0170] Example 1.

[0171] (Preparation of non-aqueous electrolyte)

[0172] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and monofluorobenzene (FB) in a volume ratio of 9:1 and then dissolving LiFSI at a concentration of 2.4 M.

[0174] (Secondary battery manufacturing)

[0175] Cathode active material (Li(Ni 0.8 Mn 0.1 Co 0.1 A positive electrode active material slurry (solid content 55 wt%) was prepared by adding a conductive material (carbon black) and a binder (polyvinylidene fluoride (PVDF)) to N-methyl-2-pyrrolidone (NMP) in a weight ratio of 90:5:5. The positive electrode active material slurry was coated onto a positive electrode current collector (Al thin film) with a thickness of 20 μm, and a positive electrode was manufactured by drying and rolling.

[0176] Next, a cathode (Li / Cu) was prepared by bonding 10 μm lithium metal to a 20 μm thick copper foil.

[0177] Next, an electrode assembly was manufactured by interposing a polyethylene porous film between the anode and cathode prepared above, and then the assembly was placed in a battery case, the prepared non-aqueous electrolyte was injected into each, and the assembly was sealed to manufacture a lithium secondary battery (see Table 1 below).

[0179] Example 2.

[0180] (Preparation of non-aqueous electrolyte)

[0181] Dimethyl carbonate (DMC):monofluorobenzene (FB) was mixed in a volume ratio of 8:2, and then LiFSI was dissolved at a concentration of 2.0 M to prepare a non-aqueous electrolyte for a lithium secondary battery.

[0183] (Secondary battery manufacturing)

[0184] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared in Example 1 was used instead of the non-aqueous electrolyte prepared in Example 1 (see Table 1 below).

[0186] Example 3.

[0187] (Preparation of non-aqueous electrolyte)

[0188] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and monofluorobenzene (FB) in a volume ratio of 7:3 and then dissolving LiFSI at a concentration of 1.5 M.

[0190] (Secondary battery manufacturing)

[0191] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared in Example 1 was used instead of the non-aqueous electrolyte prepared in Example 1 (see Table 1 below).

[0193] Example 4.

[0194] (Preparation of non-aqueous electrolyte)

[0195] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether in a volume ratio of 9:1, and then dissolving LiFSI at a concentration of 2.4 M.

[0197] (Secondary battery manufacturing)

[0198] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared in Example 1 was used instead of the non-aqueous electrolyte prepared in Example 1 (see Table 1 below).

[0200] Example 5.

[0201] (Preparation of non-aqueous electrolyte)

[0202] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether in a volume ratio of 8:2, and then dissolving LiFSI at a concentration of 2.0 M (see Table 1 below).

[0204] (Secondary battery manufacturing)

[0205] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared above was used instead of the non-aqueous electrolyte prepared in Example 1.

[0207] Example 6.

[0208] (Preparation of non-aqueous electrolyte)

[0209] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether in a volume ratio of 7:3, and then dissolving LiFSI at a concentration of 1.5 M (see Table 1 below).

[0211] (Secondary battery manufacturing)

[0212] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared in Example 1 was used instead of the non-aqueous electrolyte prepared in Example 1 (see Table 1 below).

[0214] Example 7.

[0215] (Preparation of non-aqueous electrolyte)

[0216] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether in a volume ratio of 9:1, and then dissolving LiFSI at a concentration of 2.4 M.

[0218] (Secondary battery manufacturing)

[0219] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared in Example 1 was used instead of the non-aqueous electrolyte prepared in Example 1 (see Table 1 below).

[0221] Example 8.

[0222] (Preparation of non-aqueous electrolyte)

[0223] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether in a volume ratio of 8:2, and then dissolving LiFSI at a concentration of 2.0 M.

[0225] (Secondary battery manufacturing)

[0226] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared in Example 1 was used instead of the non-aqueous electrolyte prepared in Example 1 (see Table 1 below).

[0228] Example 9.

[0229] (Preparation of non-aqueous electrolyte)

[0230] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether in a volume ratio of 7:3, and then dissolving LiFSI at a concentration of 1.5 M.

[0232] (Secondary battery manufacturing)

[0233] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared in Example 1 was used instead of the non-aqueous electrolyte prepared in Example 1 (see Table 1 below).

[0235] Example 10.

[0236] (Secondary battery manufacturing)

[0237] Cathode active material (Li(Ni 0.6 Mn 0.2 Co 0.2A positive electrode active material slurry (solid content 55 wt%) was prepared by adding a conductive material (carbon black) and a binder (polyvinylidene fluoride (PVDF)) to N-methyl-2-pyrrolidone (NMP) in a weight ratio of 90:5:5. The positive electrode active material slurry was coated onto a positive electrode current collector (Al thin film) with a thickness of 20 μm, and a positive electrode was manufactured by drying and rolling.

[0238] Next, a cathode (Li / Cu) was prepared by bonding 10 μm lithium metal to a 20 μm thick copper foil.

[0239] Next, an electrode assembly was prepared by interposing a polyethylene porous film between the anode and cathode prepared above, and then the assembly was placed in a battery case, the non-aqueous electrolyte prepared in Example 3 was injected into each, and the assembly was sealed to manufacture a lithium secondary battery (see Table 1 below).

[0241] Example 11.

[0242] (Secondary battery manufacturing)

[0243] Cathode active material (Li(Ni 0.6 Mn 0.2 Co 0.2 A positive electrode active material slurry (solid content 55 wt%) was prepared by adding a conductive material (carbon black) and a binder (polyvinylidene fluoride (PVDF)) to N-methyl-2-pyrrolidone (NMP) in a weight ratio of 90:5:5. The positive electrode active material slurry was coated onto a positive electrode current collector (Al thin film) with a thickness of 20 μm, and a positive electrode was manufactured by drying and rolling.

[0244] Next, a cathode (Li / Cu) was prepared by bonding 10 μm lithium metal to a 20 μm thick copper foil.

[0245] Next, an electrode assembly was prepared by interposing a polyethylene porous film between the anode and cathode prepared above, and then the assembly was placed in a battery case, the non-aqueous electrolyte prepared in Example 6 was injected into each, and the assembly was sealed to manufacture a lithium secondary battery (see Table 1 below).

[0247] Example 12.

[0248] (Secondary battery manufacturing)

[0249] Cathode active material (Li(Ni 0.6 Mn 0.2 Co 0.2 A positive electrode active material slurry (solid content 55 wt%) was prepared by adding a conductive material (carbon black) and a binder (polyvinylidene fluoride (PVDF)) to N-methyl-2-pyrrolidone (NMP) in a weight ratio of 90:5:5. The positive electrode active material slurry was coated onto a positive electrode current collector (Al thin film) with a thickness of 20 μm, and a positive electrode was manufactured by drying and rolling.

[0250] Next, a cathode (Li / Cu) was prepared by bonding 10 μm lithium metal to a 20 μm thick copper foil.

[0251] Next, an electrode assembly was prepared by interposing a polyethylene porous film between the anode and cathode prepared above, and then the assembly was placed in a battery case, the non-aqueous electrolyte prepared in Example 9 was injected into each, and the assembly was sealed to manufacture a lithium secondary battery (see Table 1 below).

[0253] Example 13.

[0254] A non-aqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1, except that LiPF6 was included instead of LiFSI as the lithium salt when preparing the non-aqueous electrolyte (see Table 1 below).

[0256] Example 14.

[0257] A non-aqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 2, except that LiPF6 was included instead of LiFSI as the lithium salt when preparing the non-aqueous electrolyte (see Table 1 below).

[0259] Example 15.

[0260] A non-aqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 3, except that LiPF6 was included instead of LiFSI as the lithium salt when preparing the non-aqueous electrolyte (see Table 1 below).

[0262] Example 16.

[0263] A non-aqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 1, except that 1.8M LiPF6 was included as the lithium salt instead of 2.4M LiFSI when preparing the non-aqueous electrolyte (see Table 1 below).

[0265] Example 17.

[0266] A non-aqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 2, except that 1.4M LiPF6 was included as the lithium salt instead of 2.0M LiFSI when preparing the non-aqueous electrolyte (see Table 1 below).

[0268] Example 18.

[0269] A non-aqueous electrolyte and a lithium secondary battery were prepared in the same manner as in Example 3, except that 0.9M LiPF6 was included as the lithium salt instead of 1.5M LiFSI when preparing the non-aqueous electrolyte (see Table 1 below).

[0271] Comparative Example 1.

[0272] (Preparation of non-aqueous electrolyte)

[0273] A non-aqueous electrolyte for a lithium secondary battery was prepared by dissolving LiFSI in dimethyl carbonate (DMC) at a concentration of 2.8 M.

[0275] (Secondary battery manufacturing)

[0276] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared in Example 1 was used instead of the non-aqueous electrolyte prepared in Example 1 (see Table 1 below).

[0278] Comparative Example 2.

[0279] (Preparation of non-aqueous electrolyte)

[0280] A non-aqueous electrolyte for a lithium secondary battery was prepared by dissolving LiFSI in dimethyl carbonate (DMC) at a concentration of 2.4 M.

[0282] (Secondary battery manufacturing)

[0283] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared in Example 1 was used instead of the non-aqueous electrolyte prepared in Example 1 (see Table 1 below).

[0285] Comparative Example 3.

[0286] (Secondary battery manufacturing)

[0287] Cathode active material (Li(Ni 0.6 Mn 0.2 Co 0.2 A positive electrode active material slurry (solid content 55 wt%) was prepared by adding a conductive material (carbon black) and a binder (polyvinylidene fluoride (PVDF)) to N-methyl-2-pyrrolidone (NMP) in a weight ratio of 90:5:5. The positive electrode active material slurry was coated onto a positive electrode current collector (Al thin film) with a thickness of 20 μm, and a positive electrode was manufactured by drying and rolling.

[0288] Next, a cathode (Li / Cu) was prepared by bonding 10 μm lithium metal to a 20 μm thick copper foil.

[0289] Next, an electrode assembly was prepared by interposing a polyethylene porous film between the anode and cathode prepared above, and then the assembly was placed in a battery case, the non-aqueous electrolyte prepared in Comparative Example 2 was injected into each, and the assembly was sealed to manufacture a lithium secondary battery (see Table 1 below).

[0291] Comparative Example 4.

[0292] (Preparation of non-aqueous electrolyte)

[0293] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether in a 4:6 volume ratio and then dissolving LiFSI. At this time, as the amount of 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether, which is the second non-aqueous solvent, increased, the solubility of the lithium salt decreased, and LiFSI was dissolved at a maximum concentration of 1 M.

[0295] (Secondary battery manufacturing)

[0296] A lithium secondary battery was manufactured in the same manner as in Comparative Example 1, except that the non-aqueous electrolyte prepared above was used instead of the non-aqueous electrolyte prepared in Comparative Example 1 (see Table 1 below).

[0298] Comparative Example 5.

[0299] (Preparation of non-aqueous electrolyte)

[0300] A non-aqueous electrolyte for a lithium secondary battery was prepared by mixing dimethyl carbonate (DMC) and 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether in a volume ratio of 9.5:0.5, and then dissolving LiFSI at a concentration of 2.8 M.

[0302] (Secondary battery manufacturing)

[0303] A lithium secondary battery was manufactured in the same manner as in Comparative Example 1, except that the non-aqueous electrolyte prepared above was used instead of the non-aqueous electrolyte prepared in Comparative Example 1 (see Table 1 below).

[0305] In Table 1 below, the abbreviations of the compounds each have the following meanings.

[0306] LiFSI: Lithium fluorosulfonyl imide (LiN(SO2F)2)

[0307] DMC: Dimethyl carbonate

[0308] FB: Monofluorobenzene (FB)

[0309] NCM811: Li(Ni 0.8 Mn 0.1 Co 0.1 )O2

[0310] NCM622: Li(Ni 0.6 Mn 0.2 Co 0.2 )O2

[0311] lithium salt First non-aqueous solvent Second non-aqueous solvent Volume ratio of first non-aqueous solvent to second non-aqueous solvent anode Example 1 2.4 M LiFSI DMC FB 9:1 NCM811 Example 2 2.0 M LiFSI DMC FB 8:2 NCM811 Example 3 1.5 M LiFSI DMC FB 7:3 NCM811 Example 4 2.4 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether 9:1 NCM811 Example 5 2.0 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether 8:2 NCM811 Example 6 1.5 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether 7:3 NCM811 Example 7 2.4 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether 9:1 NCM811 Example 8 2.0 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether 8:2 NCM811 Example 9 1.5 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether 7:3 NCM811 Example 10 1.5 M LiFSI DMC FB 7:3 NCM622 Example 11 1.5 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether 7:3 NCM622 Example 12 1.5 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether 7:3 NCM622 Example 13 2.4 M LiPF6 DMC FB 9:1 NCM811 Example 14 2.0 M LiPF6 DMC FB 8:2 NCM811 Example 15 1.5 M LiPF6 DMC FB 7:3 NCM811 Example 16 1.8 M LiPF6 DMC FB 9:1 NCM811 Example 17 1.4 M LiPF6 DMC FB 8:2 NCM811 Example 18 0.9 M LiPF6 DMC FB 7:3 NCM811 Comparative Example 1 2.8 M LiFSI DMC - 10:0 NCM811 Comparative Example 2 2.4 M LiFSI DMC - 10:0 NCM811 Comparative Example 3 2.4 M LiFSI DMC - 10:0 NCM622 Comparative Example 4 1.0 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether 4:6 NCM811 Comparative Example 5 2.8 M LiFSI DMC 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether 9.5:0.5 NCM811

[0313] Experimental Example

[0314] Experimental Example 1. Evaluation of Viscosity of Non-Aqueous Electrolyte

[0315] The viscosity of the non-aqueous electrolytes prepared in Examples 1 to 18 and the non-aqueous electrolytes prepared in Comparative Examples 1, 3, and 5 was measured at 25°C using a Brookfield LV DV-II + Pro Viscometer (cone-plate type, torque 90%, spindle #42, sample loading 1 mL). The results are shown in Table 2 below.

[0316] Non-aqueous electrolyte viscosity (cp) Example 1 8.60 Example 2 4.86 Example 3 1.03 Example 4 8.83 Example 5 5.26 Example 6 4.19 Example 7 8.03 Example 8 4.42 Example 9 3.34 Example 10 1.03 Example 11 4.19 Example 12 3.34 Example 13 8.90 Example 14 5.07 Example 15 2.26 Example 16 8.70 Example 17 4.99 Example 18 2.01 Comparative Example 1 12.8 Comparative Example 3 12.8 Comparative Example 5 12.2

[0318] Referring to Table 2 above, it can be seen that the viscosity of the non-aqueous electrolytes of Comparative Examples 1 to 3 and Comparative Example 5 is about 12.2 cp or higher, whereas the viscosity of the non-aqueous electrolytes prepared in Examples 1 to 18 of the present invention is about 8.90 cp or lower, indicating an improvement in viscosity. In particular, when examining the viscosity of the non-aqueous electrolytes prepared in Examples 1 to 18 of the present invention, it can be seen that the viscosity improves as the content of the fluorinated organic solvent increases.

[0320] Experimental Example 2. Evaluation of Ionic Conductivity of Non-Aqueous Electrolyte

[0321] The ionic conductivity of the non-aqueous electrolytes prepared in Examples 1 to 5, Examples 7 to 10, Example 12, Example 13, and Examples 16 to 18, and the ionic conductivity of the non-aqueous electrolytes prepared in Comparative Examples 4 and 5 were each measured at 25°C using a Multiparameter from Mettler Toledo. The results are shown in Table 3 below.

[0322] Ionic conductivity (10 -1 mS / cm) Example 1 7.52 Example 2 7.48 Example 3 7.23 Example 4 7.56 Example 5 7.80 Example 7 7.67 Example 8 8.12 Example 9 7.23 Example 10 7.23 Example 12 7.23 Example 13 4.98 Example 16 7.11 Example 17 7.07 Example 18 6.98 Comparative Example 4 3.22 Comparative Example 5 7.21

[0324] Referring to Table 3 above, the ionic conductivity of the non-aqueous electrolytes prepared in Examples 1 to 5, Examples 7 to 10, and Examples 12 and 16 to 18 is approximately 6.98 × 10⁻⁶. -1 While it is greater than mS / cm, the ionic conductivity of the non-aqueous electrolyte prepared in Comparative Example 4 is 3.22×10 -1 It can be seen that the ionic conductivity has decreased to mS / cm. That is, in the case of the non-aqueous electrolyte prepared in Comparative Example 4, as the content of the second non-aqueous solvent, a fluorine-based organic solvent that does not form a coordination bond with the lithium salt, increases, LiFSI is not well dissolved, and as a result, it can be seen that the ionic conductivity has significantly deteriorated compared to the non-aqueous electrolyte prepared in Example 9.

[0325] In addition, in the case of the non-aqueous electrolyte prepared in Comparative Example 5, as the volume ratio of the second non-aqueous solvent decreased, it can be seen that the ionic conductivity decreased compared to the non-aqueous electrolytes prepared in Examples 1 to 5, Examples 7 to 10, and Example 12.

[0326] Meanwhile, it can be seen that the non-aqueous electrolyte prepared in Examples 16 to 18, which contains LiPF6 instead of LiFSI as the lithium salt, has a reduced ionic conductivity compared to the non-aqueous electrolyte prepared in Examples 1 to 5, 7 to 10, and 12, which contain LiFSI as the lithium salt. In particular, in the case of the non-aqueous electrolyte of Example 13, which contains a high concentration of LiPF6, it can be seen that the ionic conductivity is significantly degraded due to the increase in viscosity compared to the non-aqueous electrolyte prepared in Examples 1 to 5, 7 to 10, and 12, or the non-aqueous electrolyte of Comparative Example 5, which contains a high concentration of LiFSI.

[0328] Experimental Example 3. Lithium (Li + ) Ion Diffusion Evaluation Experiment

[0329] Li in each non-aqueous electrolyte prepared in Examples 1 to 3 and Comparative Examples 1 and 2 above + The diffusivity of ions was evaluated, and the results are shown in Table 4 below. Li + The diffusivity of ions was evaluated using the 7Li DOSY NMR method with a Bruker 600MHz Advance III HD instrument.

[0330] Li + Diffusion rate (10 -10 m 2 / S) Example 1 1.22 Example 2 2.11 Example 3 3.16 Comparative Example 1 0.88 Comparative Example 2 1.21

[0332] Referring to Table 4 above, the lithium ion diffusivity in the non-aqueous electrolytes of Comparative Examples 1 and 2 is 1.21 × 10⁻⁶ -10 m 2 While / S or less, the lithium ion diffusivity in the non-aqueous electrolyte of Examples 1 to 3 of the present invention is 1.22 × 10⁻⁶ -10 m 2 It can be seen that it has been improved beyond / S.

[0334] Experimental Example 4. IR band area ratio evaluation experiment

[0335] The IR spectra for each non-aqueous electrolyte prepared in Examples 1 to 3 and Comparative Examples 1 and 2 were measured using FT-IR spectroscopy in ATR mode, and after integrating the obtained peaks, the values ​​were substituted into Equation 1 below to determine the Free DMC solvent and Li + The IR band area ratio of the coordinated DMC solvent was calculated. The calculated IR band area ratios are shown in Table 5 below. (In this case, for the fluorinated organic solvent, which is the second non-aqueous solvent that does not form a coordination bond with the lithium salt, IR band confirmation was not possible.)

[0336] [Equation 1]

[0337] IR band area ratio = Area of ​​Li + coordinated DMC / Area of ​​Free DMC

[0338] IR band area ratio Example 1 2.31 Example 2 2.3 Example 3 2.32 Comparative Example 1 2.3 Comparative Example 2 2.09

[0340] Referring to Table 5 above, it can be seen that the IR band area ratio of the non-aqueous electrolyte of Comparative Example 1, which contains 2.8M of lithium salt and does not contain the second non-aqueous solvent, a fluorine-based organic solvent, is 2.3, whereas the IR band area ratio of the non-aqueous electrolyte of Comparative Example 2, in which the concentration of the lithium salt is lowered to 2.4M, is lowered to 2.09 due to the decrease in the concentration of the lithium salt.

[0341] In other words, it can be seen that when the concentration of the lithium salt decreases, the proportion of the carbonate solvent, which is the first non-aqueous solvent participating in the dissociation of the lithium salt, decreases, and the proportion of the Free DMC solvent increases.

[0343] Meanwhile, in the case of the non-aqueous electrolytes of Examples 1 to 3, in which the concentration of lithium salt is 2.4M, 2M, and 1.5M respectively compared to Comparative Example 1, it can be seen that the IR band area ratio is 2.3 to 2.32, which is similar to the IR band area ratio (2.3) of the non-aqueous electrolyte of Comparative Example 1.

[0344] That is, it can be seen that when the content of a fluorine-based organic solvent, which is a second non-aqueous solvent that does not form coordination bonds with the lithium salt, increases instead of having a low concentration of lithium salt as in the non-aqueous electrolytes of Examples 1 to 3 of the present invention, the proportion of the carbonate solvent, which is a first non-aqueous solvent that participates in the dissociation of the lithium salt, increases even under conditions of low lithium salt concentration. Therefore, it can be seen that in order to increase the electrolyte impregnation properties in the present invention, a lithium secondary battery can be manufactured using a low-viscosity non-aqueous electrolyte containing a fluorine-based organic solvent as the second non-aqueous solvent and having a low concentration of lithium salt.

[0346] Experimental Example 5. Evaluation of Cycle Characteristics

[0347] The secondary batteries prepared in Examples 1 to 12 and Examples 16 to 18 and the secondary batteries prepared in Comparative Examples 1 to 5 were each subjected to an electrolyte impregnation process at 25°C for 1 day, then charged at 25°C with a constant current and constant voltage to 4.2 V, and then discharged at 0.1C with a constant current to 3.0 V.

[0348] Next, it was charged to 4.2V with a constant current and constant voltage at 0.2C, and then discharged to 3.0V with a constant current of 2C. The above charging and discharging cycles were performed 150 times, with each cycle constituting one cycle.

[0349] At this time, the number of cycles at which 80% of the capacity is maintained relative to the capacity measured after the initial formation process was determined, and the results are shown in Table 6 below.

[0351] Experimental Example 6. Evaluation of Dosage Characteristics

[0352] The secondary batteries prepared in Examples 1 to 12 and Examples 16 to 18 and the secondary batteries prepared in Comparative Examples 1 to 5 were each subjected to an electrolyte impregnation process at 25°C for 1 day, then charged at 25°C with a constant current and constant voltage to 4.2 V, and then discharged at 0.1C with a constant current to 3.0 V.

[0353] Next, the device was charged to 4.2V with a constant current and constant voltage at 0.2C and discharged to 3.0V with a constant current at 3C, and the discharge capacity measured using a PNE-0506 charger / discharger (Manufacturer: PNE Solution Co., Ltd., 5V, 6A) is shown in Table 6 below.

[0354] 80% discharge capacity retention rate (number of cycles) Discharge capacity (%) at 3C Example 1 85 86 Example 2 90 89 Example 3 105 93 Example 4 82 85 Example 5 91 87 Example 6 94 89 Example 7 86 86 Example 8 92 88 Example 9 98 90 Example 10 103 90 Example 11 101 91 Example 12 105 91 Example 16 78 80 Example 17 84 81 Example 18 91 81 Comparative Example 1 68 77 Comparative Example 2 43 79 Comparative Example 3 72 77 Comparative Example 4 Difficulty in evaluating cells Difficulty in evaluating cells Comparative Example 5 70 78

[0356] Referring to Table 6 above, it can be seen that the lithium secondary batteries manufactured in Examples 1 to 12 and Examples 16 to 18 of the present invention maintain a discharge capacity of 80% of the initial discharge capacity up to approximately 78 cycles later.

[0357] On the other hand, it can be seen that the discharge capacity retention rate of the lithium secondary batteries of Comparative Examples 1 to 3 and Comparative Example 5 has deteriorated compared to the examples, as the discharge capacity retention rate of most of them is measured to be 80% of the initial discharge capacity before 72 cycles.

[0358] In addition, referring to Table 6 above, it can be seen that the non-aqueous electrolytes of Comparative Examples 1 to 3 and Comparative Example 5 have a discharge capacity of about 79% or less at 3C, whereas the non-aqueous electrolytes prepared in Examples 1 to 12 and Examples 16 to 18 of the present invention have a discharge capacity improved to mostly 80% or more.

[0359] Meanwhile, the lithium secondary battery of Comparative Example 4 had low ion conductivity, so smooth battery operation was not achieved, making it difficult to evaluate the cycle characteristics and capacity characteristics of the secondary battery.

Claims

Claim 1 A cathode comprising a lithium transition metal oxide represented by the following chemical formula 1, a cathode, a separator interposed between the cathode and the cathode, and a non-aqueous electrolyte comprising a lithium salt and a non-aqueous solvent, wherein the lithium salt is composed of LiFSI and the concentration of the lithium salt is 1.5 M to 2.8 M, the non-aqueous solvent is a mixture of a first non-aqueous solvent and a second non-aqueous solvent, wherein the first non-aqueous solvent is a linear carbonate-based organic solvent and the second non-aqueous solvent is a fluorine-based organic solvent, wherein the linear carbonate-based organic solvent is at least one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethylmethyl carbonate, methylpropyl carbonate, and ethylpropyl carbonate, and the fluorine-based organic solvent is composed of a fluorine-containing aromatic organic solvent or a fluorine-containing ether organic solvent represented by the following chemical formula 2, and the volume ratio of the first non-aqueous solvent and the second non-aqueous solvent is 5:5 to 9:

1. Lithium secondary battery: [Chemical Formula 1]Li(Ni a Co b Mn c )O2 In the above formula 1, 0.6≤a≤0.9, 0.05≤b<0.3, 0.05≤c<0.3, a+b+c=1. [Formula 2] R1-O-R2 In the above formula 2, R1 and R2 are each independently an alkyl group having 1 to 10 carbon atoms that is substituted or unsubstituted with at least one fluorine element. Claim 2 In claim 1, the lithium transition metal oxide represented by the chemical formula 1 is Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 A lithium secondary battery that is )O2. Claim 3 In claim 1, the lithium transition metal oxide represented by the chemical formula 1 is Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 A lithium secondary battery that is )O2. Claim 4 delete Claim 5 delete Claim 6 A lithium secondary battery according to claim 1, wherein the volume ratio of the first non-aqueous solvent and the second non-aqueous solvent is 7:3 to 9:

1. Claim 7 A lithium secondary battery according to claim 1, wherein the linear carbonate-based organic solvent is dimethyl carbonate. Claim 8 delete Claim 9 A lithium secondary battery according to claim 1, wherein the fluorine-containing aromatic organic solvent is at least one selected from the group consisting of monofluorobenzene, 1,2-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, pentafluorobenzene, and hexafluorobenzene. Claim 10 A lithium secondary battery according to claim 9, wherein the fluorine-containing aromatic organic solvent is at least one selected from the group consisting of monofluorobenzene and 1,2-difluorobenzene. Claim 11 A lithium secondary battery according to claim 1, wherein in formula 2, R1 is an alkyl group having 2 to 8 carbon atoms substituted with at least one fluorine element, and R2 is an alkyl group having 1 to 7 carbon atoms substituted with at least one fluorine element. Claim 12 A lithium secondary battery according to claim 11, wherein in the formula 2, R1 is an alkyl group having 2 to 6 carbon atoms substituted with at least one fluorine element, R2 is an alkyl group having 1 to 5 carbon atoms substituted with at least one fluorine element, and n is an integer among 1 to 5. Claim 13 A lithium secondary battery according to claim 1, wherein the fluorine-containing ether organic solvent is 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether or 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether. Claim 14 A lithium secondary battery according to claim 1, wherein the non-aqueous electrolyte further comprises at least one additional additive selected from the group consisting of cyclic carbonate compounds, halogen-substituted carbonate compounds, sulfone compounds, sulfate compounds, phosphate compounds, borate compounds, nitrile compounds, amine compounds, silane compounds, and lithium salt compounds.

Citation Information

Patent Citations

  • Electrolyte solutions for electrochemical energy devices

    KR1020070100827A

  • Rechargeable lithium battery

    KR1020190026429A

  • Lithium secondary battery of improved safety of nail penetration

    KR1020180013103A

  • Polymer electrolyte for secondary battery and secondary battery comprising same

    WO2019107855A1